Peningkatan Produktivitas dan Pendapatan Masyarakat Melalui Pengelolahan Limbah Pertanian - Tasya Wislim; Solfema Solfema; Lili Dasa Putri (Jurnal Bintang Pendidikan Indonesia, 2025)
Effective agricultural waste management has a huge potential to increase community productivity and income. Agricultural waste, often considered a problem, can be processed into valuable resources such as organic fertilizer, biogas, and animal feed. By utilizing organic fertilizer from agricultural waste, soil fertility can be enhanced and dependence on chemical fertilizers can be reduced, thus contributing to increased crop yields. Biogas produced from the fermentation process of waste can be used as an alternative energy source, which in turn can reduce operational costs and increase income. Moreover, animal feed derived from agricultural waste can improve the quality and quantity of livestock production, which also contributes to changes in the income of livestock farmers. Additionally, good agricultural waste management can reduce environmental pollution and improve public health. Therefore, it is important to raise awareness and knowledge among the community about sustainable agricultural waste management practices. This needs to be complemented by adequate infrastructure and training so that waste can be processed into resources that benefit everyone.